Utilization of Short Films in Teaching Writing Review Texts to Middle School Students - Muh. Safar (PT. Anagata Sembagi Education, 2025)
This research is a qualitative literature study that examines the use of short films as a pedagogical medium to improve review writing skills in high school students in Indonesia. The gap between the curriculum demands of in-depth understanding, critical evaluation, and structured arguments and the descriptive nature of student writing emphasizes the need for authentic, engaging, and culturally relevant media. Short films, with their dense narratives, rich visual-auditorial stimuli, and measured duration, enable a holistic viewing experience that serves as the basis for specific assessments of plot, characters, cinematic style, and thematic messages. The proposed learning framework includes pre-viewing (schema activation, prediction), directed viewing/paused viewing (multimodal critical observation), post-viewing (evaluative discussion HOTS; think pair share; gallery critique), and review writing based on an analytical rubric (orientation, interpretation, evaluation, summary, filmic evidence). Literature data was obtained through database searches (Google Scholar, Garuda, DOAJ, ERIC), rigorously selected, and analyzed through open, axial, and selective coding with source triangulation. The findings synthesize evidence that short films improve motivation, multimodal literacy, writing structure, and argument quality, while also creating opportunities for differentiation, formative assessment, and technology/LMS integration to strengthen classroom practice and action research. The implications are that teachers can utilize transparent rubrics, incremental digital feedback, and youth-themed film resources to align writing instruction with the Pancasila Student Profile and encourage further classroom-based research.